Salicylaldehyde Benzoylhydrazone Protects Against Ferroptosis in Models of Neurotoxicity and Behavioural Dysfunction, In Vitro and In Vivo - Niamh C. Clarke; Ellen McCabe; Lasse D. Jensen; Bernadette S. Creaven; Derek A. Costello (Journal of Molecular Neuroscience, 2025)
Metal dyshomeostasis in the brain is a key feature of many neuropathologies, including hypoxic and traumatic injury and chronic conditions such as Alzheimer’s and Parkinson’s disease. Ferroptosis is a form of cell death driven by the intracellular accumulation of iron. This is primarily characterised by a loss in endogenous antioxidant capacity and uncontrolled lipid peroxidation. Ferroptosis has been reported to underlie the pathology associated with several neurological and neurodegenerative conditions and has, therefore, become an attractive target for therapeutic intervention. Salicylaldehyde benzoylhydrazone (SBH) is a specialised hydrazone agent, known for its antibacterial and anticancer properties. It has robust metal-chelating capacity, with a particular affinity for complexing with iron and copper. The current study sought to investigate the potential of SBH to act as an anti-ferroptotic agent and to alleviate the neurotoxic and dysfunctional consequences of iron overload. We demonstrate that SBH can alleviate the death of HT22 hippocampal neurons, induced by exposure to the iron donor, ferric ammonium citrate (FAC). This was accompanied by a reduction in intracellular iron and lipid peroxidation, and alleviation of hallmark changes in gene expression indicative of ferroptosis. Using FAC-incubated zebrafish larvae as an in vivo model of iron overload, we reveal that SBH can reduce the mortality and toxicity associated with FAC exposure. Moreover, we report a FAC-mediated dysfunction in intrinsic sensorimotor reflex behaviour, which is restored by SBH. Taken together, our findings highlight SBH as an anti-ferroptotic agent and support its further investigation as a potential neurotherapeutic for conditions associated with iron dysregulation.